Managing public finances in a small developing economy : the case of Barbados (Praeger WestportUS, 2001)
Discusses how Barbados fashioned an approach to public finance management that permitted it to become the leading developing country in the Human Development Index prepared by UNDP while achieving moderate rates of growth and maintaining macroeconomic stability.
Keywords: PUBLIC FINANCE